Insulin augments tumor necrosis factor-alpha stimulated expression of vascular cell adhesion molecule-1 in vascular endothelial cells - Mackesy Daniel Z; Goalstone Marc L (BMC, 2011)
Abstract Background Atherosclerosis is an inflammatory disease that is marked by increased presence of Tumor Necrosis Factor-alpha (TNFα), increased expression of Vascular Cell Adhesion Molecule-1 (VCAM-1), increased presence of serum monocytes and activation of the canonical inflammatory molecule, Nuclear Factor Kappa-B (NFκB). Hyperinsulinemia is a hallmark of insulin resistance and may play a key role in this inflammatory process. Methods Using Western blot analysis, immunocytochemistry, flow cytometry and biochemical inhibitors, we measured changes in VCAM-1 protein expression and NFκB translocation in vascular endothelial cells in the presence of TNFα and/or hyperinsulinemia and in the absence or presence of kinase pathway inhibitors. Results We report that hyperinsulinemia augmented TNFα stimulated increases in VCAM-1 protein greater than seen with TNFα alone and decreased the time in which VCAM-1 translocated to the cell surface. We also observed that in the presence of Wortmannin, a biochemical inhibitor of phosphatidylinositol 3-kinase (a hallmark of insulin resistance), VCAM-1 expression was greater in the presence of TNFα plus insulin as compared to that seen with insulin or TNFα alone. Additionally, nuclear import of NFκB occurred sooner in the presence of insulin and TNFα together as compared to each alone, and in the presence of Wortmannin, nuclear import of NFκB was greater than that seen with insulin and TNFα alone. Conclusions hyperinsulinemia and insulin resistance appear to augment the inflammatory effects of TNFα on VCAM-1 expression and NFκB translocation, both of which are markers of inflammation in the vasculature.